Autopercepção da saúde bucal associada ao estado nutricional, consumo alimentar e componentes da sarcopenia em pessoas idosas longevas independentes funcionais - Isabela Moraes Vargas (2023)
Introduction: Globally, according to the World Health Organization, life expectancy has increased by more than 6 years between 2000 and 2019, thus the number of people aged 80 years or over is rising ever faster than the number aged 65 or above. Aging is considered the main predictor of fraily and so, it is important that elderly individuals maintain their physical, mental and social wellbeing. Changes that may occur throughout the aging process, such as loss of dental elements, worsening of chewing and food consumption, and reduction of skeletal muscle mass and strength, can have an impact on the functionality and quality of life of elderly people. In this context, it is important to study these variables with a focus on healthy aging. Objectives: To evaluate the self-perception of oral health and its relationship with nutritional status, food consumption, and components of sarcopenia, in functionally independent long- lived elderly people. Method: This cross-sectional study comprised elderly outpatients attending the Healthy Aging Outpatient Clinic, Jenny de Andrade Faria Institute, Hospital das Clínicas of the Federal University of Minas Gerais. Octagenarian and those over 80 years old plus with no established functional impairment were included. Oral health was examined, and self-perception was assessed using the Oral Health Impact Profile questionnaire (OHIP-14). Food consumption was analyzed through the food record of three nonconsecutive days. Body composition was assessed by bioelectrical impedance and strength by maximum handgrip test. Statistical analyzes were performed using the Stata ® program. The sample was dichotomized by gender and median OHIP score. Results: Ninety elderly outpatients (mean age, 86,6 ± 5,4 years; 57,8% females) were included. The total OHIP score ranged from 0 to 29, with a median of 1.5 points. The group with the lowest OHIP score considered chewing to be good (p<0.001), had less need to change the texture of food, had less difficulty chewing hard foods (p=0.001), occlusion with at least 4 molars (p= 0.031), less partial loss of teeth (p=0.044), and xerostomia (p=0.01). Edentulism in both dental arches was found in 50 (55.5%), with only 37 (41.1%) using prostheses in both arches. The ingestion of calories, proteins, and fibers, the anthropometric, body composition, and physical tests data did not show differences about the OHIP score. Conclusion: Even with the high prevalence of edentulism in the studied sample, self-perception of oral health is good. The oral health of the elderly people studied is not reflected in the intake of nutrients, nutritional status, physical tests, and functionality. It is important to know the patients’ feelings and expectations, to prioritize problems that have an impact on quality of life and functionality.